PENGARUH BRAND IMAGE DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN SMARTPHONE IPHONE DI KECAMATAN KOTA JUANG KABUPATEN BIREUEN PROVINSI ACEH - Thariq, Thariq; Syahputri, Yuni (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2025)
The purpose of this study was to determine and analyze the influence of brand image partially on purchasing decisions, to determine and analyze the influence of product quality partially on purchasing decisions and to determine and analyze the influence of brand image and product quality simultaneously on purchasing decisions for iPhone Smartphones in Kota Juang. The population in this study was the community in Kota Juang District, Bireuen Regency, Aceh Province, totaling 53,913 people. The sample in the study was 100 samples. The data collection technique used in this study was carried out by distributing questionnaires. The analysis technique used in this study was multiple linear regression, partial test (t-test), simultaneous significance test (F-test) and coefficient of determination. The results showed that there was a partial influence of brand image on purchasing decisions, there was a partial influence of product quality on purchasing decisions and there was an influence of brand image and product quality on purchasing decisions for iPhone Smartphones in Kota Juang.